A Study on Consumer Perception of Ola and Uber Taxi Services - Rajesh, Rupali; Chincholkar, Snehal (Indian Journal of Computer Science, 2018)
Organized rental cab was introduced in the Indian market in 2004 with Meru cab service and soon became popular among consumers in metropolitan cities but the actual revolution came in 2010 when app based services started, with Uber in 2013. Soon the market became competitive and consumers became more demanding. Now companies are using various strategies to increase customers as well as to retain their old customers. This study is focused on identifying the difference between Ola and Uber customers and for this data has been collected with the help of structured questionnaire. Data were collected from Mumbai and specifically from working professionals. After data collection, statistical analysis showed that females prefer Uber service over Ola but while it comes to safety, consumers feel more safe with Ola than Uber. Result of this study may help the taxi service industry to design their future marketing strategies.